Gastroenteropancreatic Neuroendocrine Neoplasms in Patients with Inflammatory Bowel Disease: An ECCO CONFER Multicentre Case Series. (1st December 2021) - Festa, Stefano; Zerboni, Giulia; Derikx, Lauranne A A P; Ribaldone, Davide Giuseppe; Dragoni, Gabriele; Buskens, Christianne; van Dijkum, Els Nieveen; Pugliese, Daniela; Panzuto, Francesco; Krela-Kaźmierczak, Iwona; Mintz, Hilla Reiss; Shitrit, Ariella Bar-Gil; et al.
Abstract: Background: Gastroenteropancreatic neuroendocrine neoplasms [GEP-NENs] have rarely been reported in association with inflammatory bowel diseases [IBDs]. Methods: An ECCO COllaborative Network For Exceptionally Rare case reports project [ECCO-CONFER] collects cases of GEP-NENs diagnosed in patients with IBD. Results: GEP-NEN was diagnosed in 100 IBD patients; 61% female, 55% Crohn's disease, median age 48 years (interquartile range [IQR] 38-59]). The most common location was the appendix [39%] followed by the colon [22%]. Comprehensive IBD-related data were available for 50 individuals with a median follow-up of 30 months [IQR 11-70] following NEN diagnosis. Median duration of IBD at NEN diagnosis was 84 months [IQR 10-151], and in 18% of cases NEN and IBD were diagnosed concomitantly. At diagnosis, 20/50 were stage-I [T1N0M0], and 28/50 were graded G1 [ki67 ≤2%]. Incidental diagnosis of NEN and concomitantly IBD diagnosis were associated with an earlier NEN stage [ p = 0.01 and p = 0.02, respectively]. Exposure to immunomodulatory or biologic therapy was not associated with advanced NEN stage or grade. Primary GEP-NEN were more frequently found in the segment affected by IBD [62% vs 38%]. At the last follow-up data, 47/50 patients were alive, and only two deaths were related to NEN. Conclusions: In the largest case series to date, prognosis of patients with GEP-NEN and IBD seems favourable. Incidental NEN diagnosis correlates with an earlier NEN stage, and IBD-related therapies are probably independent of NEN stage and grade. The association of GEP-NEN location and the segment affected by IBD may suggest a possible role of inflammation in NEN tumorigenesis